The calm after the storm?: the tricky path to restoring the enjoyment of individual rights in Intimate Partner Violence cases - Amato, Rosanna (Oñati Socio-Legal Series, 2022)
Intimate Partner Violence (IPV) is the main pathology that occurs within interpersonal relations, and women are the chief victims in an overwhelming majority of cases. At present, a well-established international legal framework is in place that defines IPV as violating internationally recognized human rights. However, the application of these standards has proven difficult because it requires multilayered arrangements to be effective. This paper investigates whether and how police authorities and the justice system - as parts of the victims’ support network - can assist victims in escaping from violence and restoring normality to their lives. The focus is on the gap between the law in the book and the law in action. To this end, the paper presents the findings of an Italian case study based on both document analysis and field research. The main aim is to bring to light organizational problems that can seriously jeopardize the effectiveness of systems to shield IPV victims and the full enjoyment of their individual rights.